PEMBELAJARAN MATEMATIKA YANG MENYENANGKAN DENGAN METODE MATHEMAGICS - Meria Ultra Gusteti (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
The background to this research problem begins with the results of observations where students are weak in performing arithmetic operations so students need a long time to perform simple calculations. Besides taking a long time, students are also weak in stacked calculations. For example in addition, where there are students who forget to put inserts, so the inserts are not added up which results in erroneous results. Students have difficulty solving questions with more than two numbers and students rely more on calculators or cell phones (hand phones) for calculating. Then the paradigm which states that mathematics is a complex subject makes students less interested in this lesson. To overcome this, it is necessary to update learning methods, including using the mathemagics. In this mathematics method calculations, are given in a simple and interesting way so that students are more motivated to learn mathematics and instill in students that mathematics is fun. The purpose of this study was to find out whether the learning outcomes of students who were taught with mathemagics were better than the learning outcomes of students who were taught without mathemagics. This research is experimental research with a randomized control group-only design. The research population was class VII junior high school students. The research sample was taken randomly after being tested for normality, homogeneity and average similarity. Data processing of the final test results is done through hypothesis testing using the t-test. After doing the calculation, it is obtained t count > t table (1.779 > 1.645). It was also seen from the average value of the two samples, the average value of the experimental class was 72.42 while the average value of the control class was 67.63. The standard deviation of the experimental class and control class is 11.215 and 11.034. This shows that the proposed hypothesis is accepted. This means that the mathematics learning outcomes of students who are taught with mathemagics are better than those who are taught without mathemagics